An oxycodone sustained-release tablet and a preparation method thereof
Patent Information
- Application Number
- CN202611155276.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-07-31
AI Technical Summary
[0003]然而,由于盐酸羟考酮与对乙酰氨基酚在理化性质上存在显著差异,在制备过程中易出现混合不均的现象,影响缓释片的片剂质量和缓释效果
[0036] 1. This invention addresses the defect of uneven mixing that easily occurs during the preparation of acetaminophen-oxycodone sustained-release tablets. By granulating oxycodone hydrochloride and acetaminophen separately before preparing sustained-release tablets, the uniformity of mixing of active ingredients and excipients is effectively improved, the physical molding quality of sustained-release tablets is significantly improved, structural defects such as tablet cracks and fissures are avoided, the long-term stability of tablets is guaranteed, and the tablets prepared in the end have stable drug release behavior, long duration of action, and excellent sustained-release performance.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of pharmaceutical preparations, specifically relating to an acetaminophen-oxycodone sustained-release tablet and its preparation method. Background Technology
[0002] Acetaminophen-oxycodone tablets are a compound tablet composed of oxycodone hydrochloride and acetaminophen. Through different but complementary mechanisms of action in suppressing pain, they can exert a dual analgesic effect on both the central and peripheral nervous systems. Currently, the immediate-release oxycodone tablets used in China are limited to a single specification: 5mg oxycodone hydrochloride and 325mg acetaminophen, requiring four doses daily. This frequent dosing not only reduces patient compliance but also easily leads to significant peak-and-trough fluctuations in blood drug concentration, increasing the risk of adverse reactions and affecting the duration of analgesia. Therefore, there is an urgent need to develop an oxycodone sustained-release tablet with excellent sustained-release effect.
[0003] However, due to the significant differences in physicochemical properties between oxycodone hydrochloride and acetaminophen, uneven mixing is likely to occur during the preparation process, affecting the tablet quality and sustained-release effect of the sustained-release tablets. Summary of the Invention
[0004] This invention provides an acetaminophen-oxycodone sustained-release tablet and its preparation method, which ensures the high uniformity and long-term stability of the sustained-release tablet and achieves excellent sustained-release effect.
[0005] The present invention provides an acetaminophen-oxycodone sustained-release tablet, wherein the acetaminophen-oxycodone sustained-release tablet comprises a sustained-release layer and an immediate-release layer. By weight, the sustained-release layer comprises 3.5-4 parts of oxycodone hydrochloride and 130-195 parts of acetaminophen, and the immediate-release layer comprises 1-1.5 parts of oxycodone hydrochloride and 130-195 parts of acetaminophen.
[0006] The sustained-release layer is formed by mixing and pressing oxycodone hydrochloride particles, acetaminophen particles, and excipient A. The immediate-release layer is formed by mixing and pressing oxycodone hydrochloride particles, acetaminophen particles, and excipient B. The oxycodone hydrochloride particles are granulated from 4.5 to 5.5 parts of oxycodone hydrochloride and excipient A. The acetaminophen particles are granulated from 260 to 390 parts of acetaminophen and excipient B.
[0007] The internal excipient A contains 10-30 parts of microcrystalline cellulose, the internal excipient B contains 20-60 parts of microcrystalline cellulose and 15-40 parts of hydroxypropyl cellulose, the external excipient A contains 200-350 parts of polyoxyethylene, and the external excipient B contains 2-10 parts of crosslinked sodium carboxymethyl cellulose.
[0008] In some embodiments, the sustained-release layer is obtained by mixing and pressing 70%–80% oxycodone hydrochloride particles, 40%–60% acetaminophen particles, and excipient A. Preferably, the sustained-release layer is obtained by mixing and pressing 75% oxycodone hydrochloride particles, 50% acetaminophen particles, and excipient A.
[0009] In some embodiments, the immediate-release layer is obtained by mixing and pressing 20% to 30% oxycodone hydrochloride particles, 40% to 60% acetaminophen particles, and excipient B. Preferably, the immediate-release layer is obtained by mixing and pressing 25% oxycodone hydrochloride particles, 50% acetaminophen particles, and excipient B.
[0010] In some embodiments, the total weight of oxycodone hydrochloride and acetaminophen in the sustained-release tablet is 5 parts and 325 parts, respectively. Preferably, the sustained-release layer contains 3.75 parts of oxycodone hydrochloride and 162.5 parts of acetaminophen, and the immediate-release layer contains 1.25 parts of oxycodone hydrochloride and 162.5 parts of acetaminophen.
[0011] In some embodiments, the weight ratio of the polyoxyethylene to the hydroxypropyl cellulose in the sustained-release layer is 10:1 to 30:1, preferably 20:1 to 30:1, and more preferably 25:1 to 30:1.
[0012] In some embodiments, the weight ratio of acetaminophen to hydroxypropyl cellulose in the acetaminophen particles is 10:1 to 20:1, preferably 11:1 to 16.5:1, and more preferably 11:1 to 16.2:1.
[0013] In some embodiments, the weight ratio of oxycodone hydrochloride to microcrystalline cellulose in the oxycodone hydrochloride particles is 1:3 to 1:6, preferably 1:3 to 1:4.5, and more preferably 1:3 to 1:4.4.
[0014] In some embodiments, the particle size of the acetaminophen oxycodone is D90 of 100-300 μm and D50 of 50-150 μm; preferably, D90 is 120-280 μm and D50 is 60-110 μm; more preferably, D90 is 200-280 μm and D50 is 90-110 μm.
[0015] In some embodiments, the acetaminophen oxycodone granules have a loose density of 0.45~0.55 g / ml and / or a tapped density of 0.6~0.65 g / ml; preferably, the loose density is 0.47~0.54 g / ml and / or the tapped density is 0.62~0.65 g / ml; more preferably, the loose density is 0.52~0.54 g / ml and / or the tapped density is 0.62~0.63 g / ml.
[0016] In some embodiments, the acetaminophen particles have a particle size of D90 of 360-560 μm and D50 of 110-180 μm; preferably, D90 is 380-560 μm and D50 is 120-180 μm; more preferably, D90 is 420-520 μm and D50 is 140-170 μm.
[0017] In some embodiments, the acetaminophen granules have a loose density of 0.5~0.55 g / ml and / or a tapped density of 0.55~0.65 g / ml; preferably, the loose density is 0.5~0.54 g / ml and / or the tapped density is 0.59~0.65 g / ml; more preferably, the loose density is 0.53~0.54 g / ml and / or the tapped density is 0.59~0.63 g / ml.
[0018] In some embodiments, the polyoxyethylene has a molecular weight of 1,000,000 to 2,000,000, preferably 2,000,000.
[0019] In some embodiments, the added excipient A comprises 12 to 30 parts of microcrystalline cellulose; preferably, the added excipient A comprises 15 to 30 parts of microcrystalline cellulose.
[0020] In some embodiments, the added excipient B comprises 20-55 parts of microcrystalline cellulose and 20-40 parts of hydroxypropyl cellulose; preferably, the added excipient B comprises 30-51 parts of microcrystalline cellulose and 20-35 parts of hydroxypropyl cellulose.
[0021] In some embodiments, the additive A comprises 200-330 parts of polyethylene oxide; preferably, the additive A comprises 205-325 parts of polyethylene oxide.
[0022] In some embodiments, the excipient B comprises 3 to 8 parts of croscarmellose sodium; preferably, the excipient B comprises 3 to 5 parts of croscarmellose sodium.
[0023] In some embodiments, the added excipient A further includes one or more of pregelatinized starch, anhydrous citric acid, and disodium edetate; preferably, the added excipient A further includes 0.1-5 parts of pregelatinized starch, 0.1-5 parts of anhydrous citric acid, and 0.1-5 parts of disodium edetate; more preferably, the added excipient A further includes 0.5-2 parts of pregelatinized starch, 0.2-0.5 parts of anhydrous citric acid, and 0.1-3 parts of disodium edetate.
[0024] In some embodiments, the excipient A further includes one or more of microcrystalline cellulose, colloidal silica, and magnesium stearate; preferably, the excipient A further includes 100-300 parts of microcrystalline cellulose, 1-5 parts of colloidal silica, and 1-5 parts of magnesium stearate; more preferably, the excipient A further includes 140-280 parts of microcrystalline cellulose, 3-4.5 parts of colloidal silica, and 2.5-5 parts of magnesium stearate.
[0025] In some embodiments, the excipient B further includes one or more of hydroxypropyl cellulose, microcrystalline cellulose, colloidal silica, and magnesium stearate; preferably, the excipient B further includes one or more of 2-30 parts of hydroxypropyl cellulose, 1-10 parts of microcrystalline cellulose, 0.1-5 parts of colloidal silica, and 0.1-5 parts of magnesium stearate; more preferably, the excipient B further includes one or more of 5-20 parts of hydroxypropyl cellulose, 2-6 parts of microcrystalline cellulose, 0.5-2 parts of colloidal silica, and 0.5-2 parts of magnesium stearate.
[0026] The present invention also provides a method for preparing the acetaminophen-oxycodone sustained-release tablets, the method comprising the following steps:
[0027] a. Prepare oxycodone hydrochloride granules by weighing oxycodone hydrochloride and excipient A according to the prescription weight parts, and prepare acetaminophen granules by weighing acetaminophen and excipient B according to the prescription weight parts;
[0028] b. Weigh the granules from step a according to the prescription weight parts, add excipient A, and mix to prepare sustained-release granules;
[0029] c. Weigh the granules from step a according to the prescription weight parts, add excipient B, and mix to prepare immediate-release granules;
[0030] d. Press a double-layer tablet core consisting of sustained-release and immediate-release particles;
[0031] e. Double-layer core is coated.
[0032] The present invention also provides the use of the aforementioned acetaminophen-oxycodone extended-release tablets in the preparation of a medicament for the treatment of pain.
[0033] In some embodiments, the pain is postoperative pain, preferably moderate to severe postoperative pain.
[0034] This invention provides an acetaminophen-oxycodone sustained-release tablet, comprising a sustained-release layer and an immediate-release layer. By weight, the sustained-release layer comprises 3.5-4 parts of oxycodone hydrochloride and 130-195 parts of acetaminophen; the immediate-release layer comprises 1-1.5 parts of oxycodone hydrochloride and 130-195 parts of acetaminophen. The sustained-release layer is obtained by mixing and pressing oxycodone hydrochloride particles, acetaminophen particles, and excipient A; the immediate-release layer is obtained by mixing oxycodone hydrochloride particles, acetaminophen particles, and excipient B. The oxycodone hydrochloride granules are obtained by pressing together 4.5-5.5 parts of oxycodone hydrochloride and internal excipient A, and the p-acetaminophen granules are obtained by pressing 260-390 parts of p-acetaminophen and internal excipient B. Internal excipient A contains 10-30 parts of microcrystalline cellulose, internal excipient B contains 20-60 parts of microcrystalline cellulose and 15-40 parts of hydroxypropyl cellulose, external excipient A contains 200-350 parts of polyoxyethylene, and external excipient B contains 2-10 parts of crosslinked sodium carboxymethyl cellulose.
[0035] Beneficial effects:
[0036] 1. This invention addresses the defect of uneven mixing that easily occurs during the preparation of acetaminophen-oxycodone sustained-release tablets. By granulating oxycodone hydrochloride and acetaminophen separately before preparing sustained-release tablets, the uniformity of mixing of active ingredients and excipients is effectively improved, the physical molding quality of sustained-release tablets is significantly improved, structural defects such as tablet cracks and fissures are avoided, the long-term stability of tablets is guaranteed, and the tablets prepared in the end have stable drug release behavior, long duration of action, and excellent sustained-release performance.
[0037] 2. This invention further investigated the effect of the amount of hydroxypropyl cellulose in the sustained-release tablets on the flowability of acetaminophen particles and the sustained-release effect of the sustained-release tablets. By controlling the amount of hydroxypropyl cellulose, the flowability of acetaminophen particles can be improved, the mixing uniformity of active ingredients and excipients can be enhanced, and a stable and long-lasting sustained-release effect can be ensured.
[0038] 3. This invention further investigated the effect of the molecular weight of the sustained-release material (polyoxyethylene) on the sustained-release effect. By using polyoxyethylene with a specific molecular weight, the sustained-release effect can be significantly improved, achieving a long-lasting sustained-release effect comparable to that of the reference formulation. Detailed Implementation
[0039] The present invention will be further described in detail below with reference to the embodiments, but this is not intended to limit the present invention. Any equivalent substitutions made in the art based on the disclosure of the present invention shall fall within the protection scope of the present invention.
[0040] In this invention, the terms “comprising,” “including,” and “containing,” and their equivalents, shall be understood in an open, non-exclusive sense, meaning “including but not limited to,” implying that in addition to the listed elements, components, and steps, other unspecified elements, components, and steps may also be included.
[0041] In this invention, portions can be measured in milligrams.
[0042] In this invention, unless otherwise specified, "%" in the embodiments of this invention refers to mass percentage.
[0043] In this invention, all materials, reagents, or instruments whose manufacturers are not specified are conventional reagent products that can be purchased through commercial channels.
[0044] In this invention, unless specific experimental steps or conditions are specified, the conventional experimental steps or conditions described in the literature in this field can be followed.
[0045] In this invention, some experimental methods are as follows:
[0046] 1. Particle size distribution testing method:
[0047] Instrument: BT-1001 Intelligent Powder Properties Tester.
[0048] Screen aperture: 150μm, 180μm, 212μm, 250μm, 300μm, 425μm, 600μm.
[0049] Vibration frequency: 200 times / min.
[0050] Vibration time: 5 minutes.
[0051] Calculation method: After vibration, weigh the material on each screen and divide it by the total weight of the sampled particle size distribution to calculate the percentage.
[0052] 2. Particle size testing method:
[0053] According to the method for determination of particle size and particle size distribution (Chinese Pharmacopoeia 2025 Edition, Part IV, General Chapter 0982, Method III), take an appropriate amount of particles, inject them dry, and examine them according to the method (using a laser particle size analyzer based on Mie scattering theory, such as Malvern MAZ3000 or other equivalent instruments).
[0054] 3. Liquidity testing methods:
[0055] Instrument: BT-1001 Intelligent Powder Properties Tester.
[0056] Graduated cylinder: 25ml.
[0057] Vibration frequency: 200 times / min.
[0058] Vibration time: 5 minutes.
[0059] Loose density calculation: Material weight / Cylinder volume before vibration (25ml).
[0060] Tap density calculation: Material weight / Material volume after vibration.
[0061] Hausner ratio calculation: tapped density / loose density.
[0062] Liquidity assessment:
[0063] Liquidity very good good generally qualified Difference Very bad Range
[0064] Preparation Example 1: Preparation of Oxycodone Hydrochloride Granules
[0065] The preparation method is as follows:
[0066] The oxycodone hydrochloride, microcrystalline cellulose, pregelatinized starch, anhydrous citric acid, and disodium edetate were mixed according to the prescription and mixed for 30 minutes, then water was added for granulation. The mixture was wet-granulated through a 2.0 mm sieve, dried at 60°C, and then dry-granulated through a 1.0 mm sieve to obtain oxycodone hydrochloride granules.
[0067] The composition of oxycodone hydrochloride granules is shown in Table 1:
[0068] Table 1. Composition of Oxycodone Hydrochloride Granules
[0069]
[0070] Table 2. Ratio of oxycodone hydrochloride to microcrystalline cellulose in oxycodone hydrochloride granules
[0071]
[0072] Table 3. Particle size distribution of oxycodone hydrochloride.
[0073]
[0074] Table 4. Flowability of Oxycodone Hydrochloride Granules
[0075]
[0076] The results in Tables 3 and 4 show that the oxycodone hydrochloride particles of the present invention (oxycodone hydrochloride to microcrystalline cellulose ratio of 1:3 to 1:6) have a D90 of 125.5 μm to 275.6 μm, a D50 of 67.9 to 100.7 μm, and a D10 of 20.7 to 30.7 μm. The proportion of large particles larger than 425 μm is less than 5%, indicating a reasonable particle size distribution. Furthermore, the loose density is 0.47 to 0.54 g / ml, the tapped density is 0.62 to 0.63 g / ml, the Hausner ratio is less than 1.32, and the particles have good flowability, which is beneficial for subsequent mixing processes. Especially when the ratio of oxycodone hydrochloride to microcrystalline cellulose is 1:3 to 1:4.5, the particle size D90 is 207.3 μm to 275.6 μm, D50 is 90.4 to 100.7 μm, and D10 is 25.5 to 30.7 μm, resulting in better flowability (Hausner ratio below 1.25), less fine powder (fine powder percentage (0 to 150 μm) is below 81%), better particle size distribution, and better suitability for subsequent mixing processes.
[0077] Preparation Example 2: Preparation of acetaminophen granules
[0078] Acetaminophen, microcrystalline cellulose, and hydroxypropyl cellulose were mixed according to the prescription and granulated with water after 30 minutes. The mixture was then wet-granulated through a 2.0 mm sieve, dried at 60°C, and finally dry-granulated through a 1.0 mm sieve to obtain acetaminophen granules.
[0079] The composition of acetaminophen granules is shown in Table 5:
[0080] Table 5. Composition of acetaminophen granules
[0081]
[0082] Table 6. Ratio of acetaminophen to hydroxypropyl cellulose in acetaminophen granules
[0083]
[0084] Table 7. Particle size distribution of acetaminophen particles
[0085]
[0086] Table 8. Flowability Study of Acetaminophen Granules
[0087]
[0088] The results in Tables 7 and 8 show that, compared with particles 7 and 8, particles 1 to 6 of the present invention (with a ratio of acetaminophen to hydroxypropyl cellulose of 10:1 to 20:1) have particle sizes of D90 (388.7 to 554.6 μm), D50 (120.8 to 176.8 μm), and D10 (42.3 to 80.7 μm). The proportion of fine powder (0 to 150 μm) is between 43.33% and 55.67%, and the proportion of large particles (above 425 μm) is less than 20%. The particle size distribution is reasonable, and the bulk density is 0.5 to 0.54 g / ml, the tapped density is 0.59 to 0.62 g / ml, the Hausner ratio is less than 1.25, and the particles have good flowability, which is more conducive to subsequent mixing processes.
[0089] In particular, granules 1, 2, 3, and 5 (with a acetaminophen to hydroxypropyl cellulose ratio of 11:1 to 16.5:1) have particle sizes of D90 (420.3–515.7 μm), D50 (140.4–168.4 μm), and D10 (47.9–75.3 μm). The proportion of fine powder (0–150 μm) is between 46.15% and 52.38%, and the proportion of large particles (above 425 μm) is less than 16%. The particle size distribution is uniform and concentrated, and the bulk density is 0.53–0.54 g / ml, the tapped density is 0.59–0.63 g / ml, the Hausner ratio is less than 1.2, and the granules have good flowability. This avoids problems such as uneven filling and content deviation caused by excessive particle size differences and poor flowability, thus ensuring the consistency of product quality.
[0090] In granules 7 (acetaminophen to hydroxypropyl cellulose ratio of 6.2:1), large particles with a diameter of 425μm or larger account for 26.03%, resulting in poor flowability and uneven filling and large differences in hardness during granulation. In granules 8 (acetaminophen to hydroxypropyl cellulose ratio of 22.6:1), fine powder with a diameter of 0~150μm accounts for as high as 69.78%, with an overall fine particle size, poor flowability, and a high tendency to stick to the wall, separate, fly away, and fill unevenly.
[0091] Preparation Example 3: Preparation of Acetaminophen-Oxycodone Extended-Release Tablets
[0092] The prescription composition is shown in Table 9:
[0093] The preparation method is as follows:
[0094] (1) Preparation of sustained-release layer particles
[0095] Mix acetaminophen granules, oxycodone hydrochloride granules, microcrystalline cellulose, polyoxyethylene, and colloidal silica according to the prescribed amount for 30 minutes, then add magnesium stearate according to the prescribed amount and mix for 5 minutes to obtain sustained-release granules.
[0096] (2) Preparation of immediate-release layer particles
[0097] Mix acetaminophen granules, oxycodone hydrochloride granules, hydroxypropyl cellulose, microcrystalline cellulose, croscarmellose sodium, and colloidal silica according to the prescribed amount for 30 minutes, then add magnesium stearate according to the prescribed amount and mix for 5 minutes to obtain immediate-release granules.
[0098] (3) Tableting
[0099] The immediate-release granules and the sustained-release granules are pressed into a double-layer tablet core on a double-layer tablet press according to the weight of the immediate-release tablet and the weight of the sustained-release tablet.
[0100] (4) Coating
[0101] Add the gastrointestinal film coating premix to the water being stirred, and continue stirring for at least 60 minutes until the mixture is homogeneous to obtain the coating solution. Place the tablet cores in the coating pan, control the inlet air temperature to 60℃, and when the tablet bed temperature is ≥35℃, perform coating at 10 rpm, controlling the coating weight gain rate to 2%~3%.
[0102] Table 9 Tablet prescriptions for Examples 1-3
[0103]
[0104] In Examples 1-3, the oxycodone hydrochloride particles are particles I-III from Preparation Example 1, and the acetaminophen particles are particles 1-3 from Preparation Example 2.
[0105] Investigation of the dosage of polyoxyethylene and hydroxypropyl cellulose in the sustained-release layer of Examples 4-6 and Comparative Examples 1-2
[0106] The difference between Examples 4-6, Comparative Examples 1-2 and Example 2 lies in the different weight ratios of polyoxyethylene to hydroxypropyl cellulose in the sustained-release layer. The formulations of each example and comparative example are shown in Table 10, and the weight ratios of polyoxyethylene to hydroxypropyl cellulose in the sustained-release layer of each example and comparative example are shown in Table 11. The preparation method is the same as that of Preparation Example 2.
[0107] Table 10 Tablet formulations for Examples 4-6 and Comparative Examples 1-2
[0108]
[0109] In Examples 4-6 and Comparative Examples 1-2, the oxycodone hydrochloride particles were all particles II from Preparation Example 1, and the acetaminophen particles in Examples 4-6 and Comparative Examples 1-2 were particles 4-8 from Table 4.
[0110] Table 11 Weight ratio of polyoxyethylene to hydroxypropyl cellulose in the sustained-release layer
[0111]
[0112] Note: Polyoxyethylene is an external excipient in the sustained-release layer, and hydroxypropyl cellulose is an internal excipient in the acetaminophen particles of the sustained-release layer.
[0113] Example 7 and Comparative Examples 3-4: Investigation of the molecular weight of polyoxyethylene
[0114] The difference between Example 7 and Comparative Examples 3-4 and Example 2 lies in the different molecular weights of the polyethylene oxide. The molecular weights of the polyethylene oxide in each example and comparative example are shown in Table 12. The preparation method is the same as that in Example 2.
[0115] Table 12 Polyoxyethylene Parameters
[0116] Polyoxyethylene model WSR N-60K NF WSR N-12K NF WSR 1105 NF WSR 301 NF Polyoxyethylene molecular weight 2,000,000 1,000,000 900,000 4,000,000
[0117] Comparative Example 5: Preparation of Acetaminophen-Oxycodone Extended-Release Tablets
[0118] The prescription composition is shown in Table 13:
[0119] The preparation method is as follows:
[0120] (1) Preparation of sustained-release layer particles
[0121] According to the prescription, oxycodone hydrochloride, acetaminophen, hydroxypropyl cellulose, microcrystalline cellulose, pregelatinized starch, anhydrous citric acid, disodium edetate, polyoxyethylene, and colloidal silica are mixed for 30 minutes, and magnesium stearate of the prescription amount is added and mixed for 5 minutes to obtain sustained-release particles.
[0122] (2) Preparation of immediate-release layer particles
[0123] According to the prescription, oxycodone hydrochloride, acetaminophen, hydroxypropyl cellulose, microcrystalline cellulose, pregelatinized starch, anhydrous citric acid, disodium edetate, croscarmellose sodium, and colloidal silica are mixed for 30 minutes. Then, magnesium stearate is added according to the prescription and mixed for 5 minutes to obtain immediate-release granules.
[0124] (3) Tableting
[0125] The immediate-release granules and the sustained-release granules are pressed into a double-layer tablet core on a double-layer tablet press according to the weight of the immediate-release tablet and the weight of the sustained-release tablet.
[0126] (4) Coating
[0127] Add the gastrointestinal film coating premix to the water being stirred, and continue stirring for at least 60 minutes until the mixture is homogeneous to obtain the coating solution. Place the tablet cores in the coating pan, control the inlet air temperature to 60℃, and when the tablet bed temperature is ≥35℃, perform coating at 10 rpm, controlling the coating weight gain rate to 2%~3%.
[0128] Table 13 Comparative Example 5 Tablet Prescription
[0129]
[0130] Comparative Example 6: Preparation of Acetaminophen-Oxycodone Extended-Release Tablets
[0131] The prescription composition is shown in Table 14:
[0132] The preparation method is as follows:
[0133] (1) Preparation of sustained-release layer particles
[0134] Mix oxycodone hydrochloride granules, acetaminophen, hydroxypropyl cellulose, microcrystalline cellulose, polyoxyethylene, and colloidal silica according to the prescribed amount for 30 minutes, then add magnesium stearate according to the prescribed amount and mix for 5 minutes to obtain sustained-release granules.
[0135] (2) Preparation of immediate-release layer particles
[0136] Mix oxycodone hydrochloride granules, acetaminophen, hydroxypropyl cellulose, microcrystalline cellulose, croscarmellose sodium, and colloidal silica according to the prescribed amount for 30 minutes, then add magnesium stearate according to the prescribed amount and mix for 5 minutes to obtain immediate-release granules.
[0137] (3) Tableting
[0138] The immediate-release granules and the sustained-release granules are pressed into a double-layer tablet core on a double-layer tablet press according to the weight of the immediate-release tablet and the weight of the sustained-release tablet.
[0139] (4) Coating
[0140] Add the gastrointestinal film coating premix to the water being stirred, and continue stirring for at least 60 minutes until the mixture is homogeneous to obtain the coating solution. Place the tablet cores in the coating pan, control the inlet air temperature to 60℃, and when the tablet bed temperature is ≥35℃, perform coating at 10 rpm, controlling the coating weight gain rate to 2%~3%.
[0141] Table 14 Comparative Example 6 Tablet Prescription
[0142]
[0143] Comparative Example 7: Domestically available immediate-release formulation acetaminophen oxycodone tablets (trade name: Tylenol), batch number 0512B02743, specifications of oxycodone hydrochloride 5mg and acetaminophen 325mg, manufactured by SpecGx LLC.
[0144] Comparative Example 8: Reference preparation: Acetaminophen oxycodone extended-release tablets (XARTEMIS XR), batch number AE6331B.
[0145] Example 1
[0146] Evaluation of the release effect of sustained-release tablets
[0147] 1. Sample
[0148] Samples of this invention: Samples prepared in Examples 1-7;
[0149] Comparative formulation samples: samples prepared by comparative examples 1-6, sample of comparative example 7, and reference formulation of comparative example 8.
[0150] 2. Test methods:
[0151] Dissolution and release were determined according to the method of determination of dissolution and release (Chinese Pharmacopoeia 2020 Edition, Part IV, General Chapter 0931, Method II, Slurry Method (with a specific settling basket)).
[0152] Dissolution conditions:
[0153] Dissolution medium pH 1.0: Take 9 ml of hydrochloric acid, dilute with water to 1000 ml, mix well, and the solution is ready.
[0154] Dissolution medium pH 4.5: Take 1.22g sodium acetate, add 2.3ml glacial acetic acid, add water to 1000ml, shake well, and the solution is ready.
[0155] Dissolution medium pH 6.8: Take 6.8g of potassium dihydrogen phosphate, add 0.896g of sodium hydroxide, add water to 1000ml, and shake well.
[0156] Media volume: 900ml.
[0157] Sample collection: The test sample was placed in a settling basket and rotated at 150 revolutions per minute. The sample was collected after 5 min, 10 min, 15 min, 30 min, 60 min, 120 min, 240 min, 360 min, 480 min, 600 min and 720 min.
[0158] Column: Diamonsil C8, 4.6×150mm, 5µm (or a column with equivalent performance).
[0159] Mobile phase: 0.005 mol / L sodium hexanesulfonate (containing 0.1% (v / v) triethylamine, pH adjusted to 4.0 with phosphoric acid) - methanol - acetonitrile (75:10:15).
[0160] Injection volume: Acetaminophen: 10µl; Oxycodone hydrochloride: 20µl.
[0161] Detection wavelength: 214nm.
[0162] Column temperature: 40°C.
[0163] Flow rate: 1.5 ml / min.
[0164] Assay: Inject the test solution and reference solution separately into the liquid chromatograph and record the chromatograms. Calculate the dissolution amount per tablet based on peak area using the external standard method.
[0165] The f2 similarity factor is calculated as follows: 50*log{[1+1 / n∑(Rt-Tt)^2]^-0.5*100}, where n is the number of sampling points, Rt is the cumulative dissolution of the control sample (Comparative Example 2), and Tt is the cumulative dissolution of the test samples (each example and comparative example). f2 > 50 indicates that the dissolution curves of the control sample and the test sample are similar, while f2 < 50 indicates that the dissolution curves of the control sample and the test sample are not similar.
[0166] 3. Observation results:
[0167] The results of the sample investigation of the present invention are shown in Tables 15-17; the results of the comparative investigation are shown in Tables 18-20.
[0168] Table 15 Dissolution results of the samples from the examples (dissolution curves in pH 1.0 medium)
[0169]
[0170] Table 16 Dissolution results of the samples from the examples (dissolution curves in pH 4.5 medium)
[0171]
[0172] Table 17 Dissolution results of samples from the examples (dissolution curves in pH 6.8 medium)
[0173]
[0174] Table 18 Dissolution results of comparative samples (dissolution curves in pH 1.0 medium)
[0175]
[0176] Table 19 Dissolution results of comparative samples (dissolution curves in pH 4.5 medium)
[0177]
[0178] Table 20 Dissolution results of comparative samples (dissolution curves in pH 6.8 medium)
[0179]
[0180] The results in Tables 15-20 show that the dissolution behavior of the sample of the present invention is closer to that of the reference formulation, and the sustained-release effect is better. Among them:
[0181] Comparing the dissolution data of Examples 2, 4-6, and Comparative Examples 1-2, it can be seen that the amount of hydroxypropyl cellulose in the sustained-release layer (especially the weight ratio of polyoxyethylene to hydroxypropyl cellulose) affects the sample dissolution. For example, when the weight ratio of polyoxyethylene to hydroxypropyl cellulose in the sustained-release layer is between 15:1 and 35:1 (as in Examples 2, 4-6, and Comparative Example 2), the dissolution behavior is closer to that of the reference formulation, and the sustained-release effect is better. In particular, when the weight ratio of polyoxyethylene to hydroxypropyl cellulose in the sustained-release layer is between 20:1 and 30:1 (as in Examples 2, 5-6), the dissolution behavior is closest to that of the reference formulation, and the sustained-release effect is even better. Although the sample of Comparative Example 1 uses a similar formulation to that of Example 2, compared with Example 2, its sample shows a greater difference in dissolution behavior compared to the reference formulation, especially as the amount of hydroxypropyl cellulose increases, the final dissolution rate decreases.
[0182] Comparing the dissolution data of Examples 2 and 7 and Comparative Examples 3-4, it can be seen that the molecular weight of polyoxyethylene in the sustained-release layer affects the sample dissolution. For example, when WSR N-60K NF (molecular weight 2,000,000) and WSR N-12K NF (molecular weight 1,000,000) were used in Examples 2 and 7, respectively, the dissolution behavior was closer to that of the reference formulation, and the sustained-release effect was better. However, when WSR 1105 NF (molecular weight 900,000) and WSR 301 NF (molecular weight 4,000,000) were used in Comparative Examples 3-4, respectively, the dissolution behavior of the samples differed more from that of the reference formulation, especially when the f2 of oxycodone hydrochloride was below 50 in the pH 1.0 medium.
[0183] The dissolution data from Comparative Examples 2 and 5-6 show that the samples prepared by granulating oxycodone hydrochloride and acetaminophen separately exhibit dissolution behavior closer to the reference formulation, resulting in better sustained-release effects. While Comparative Examples 5-6 used the same formulation as Example 2, they differed significantly from the reference formulation by either directly preparing tablets from oxycodone hydrochloride powder and acetaminophen powder (Comparative Example 5) or granulating oxycodone hydrochloride before combining it with acetaminophen powder (Comparative Example 6).
[0184] Example 2
[0185] Evaluation of mixing uniformity
[0186] 1. Sample
[0187] The samples of this invention include: sustained-release layer particles, immediate-release layer particles, and samples (sustainable-release tablets) prepared in Examples 2, 4-6.
[0188] Comparative formulation samples: sustained-release granules and immediate-release granules (and sustained-release tablets) prepared in Comparative Examples 1-2 and 5-6.
[0189] 2. Test methods:
[0190] 2.1 Test method for particle mixing uniformity
[0191] Determined by high performance liquid chromatography (Chinese Pharmacopoeia 2025 Edition, Part IV, General Chapter 0512).
[0192] For the oxycodone hydrochloride test solution, take an appropriate amount of this product, accurately weigh it, add an appropriate amount of 8% sodium sulfate solution, transfer the entire volume to a 250 ml volumetric flask, sonicate to disperse, add about 50 ml of methanol, sonicate to completely dissolve, then dilute to the mark with 8% sodium sulfate solution, shake well, centrifuge, accurately measure an appropriate amount of supernatant, and quantitatively dilute with the mobile phase to prepare a mixed solution containing about 3 μg of oxycodone hydrochloride and 390 μg of acetaminophen per ml.
[0193] Accurately measure an appropriate amount of oxycodone hydrochloride test solution and quantitatively dilute it with the mobile phase to prepare a solution containing approximately 130 μg of acetaminophen per ml.
[0194] Take appropriate amounts of acetaminophen and oxycodone hydrochloride reference standards, accurately weigh them, dissolve them in the mobile phase, and quantitatively dilute them to prepare a mixed solution containing approximately 130 μg of acetaminophen and 2 μg of oxycodone hydrochloride per ml.
[0195] The chromatographic conditions were as follows: octylsilane-bonded silica gel was used as the stationary phase; the mobile phase was [sodium hexanesulfonate 0.005 mol / L, containing 0.1% triethylamine, pH adjusted to 4.0 with phosphoric acid]-methanol-acetonitrile (75:10:15); the flow rate was 1.5 mL / min; the column temperature was 40 °C; the detection wavelength was 214 nm; and the injection volume was 10 μL.
[0196] For the assay, accurately measure the test solution and the reference solution, inject them separately into the liquid chromatograph, and record the chromatograms. Calculate the content based on peak area using the external standard method.
[0197] RSD Calculation: RSD refers to the relative standard deviation. Relative Standard Deviation (RSD) = [Standard Deviation (S) / Arithmetic Mean (X) of the Calculated Results] × 100%
[0198]
[0199] 2.1 Test method for tablet content uniformity
[0200] For the test solution, take 10 tablets of this product and transfer them to 10 separate 250ml volumetric flasks with an appropriate amount of 8% sodium sulfate solution. Disperse the flasks by sonication. Add 50ml of methanol and sonicate to dissolve the acetaminophen and oxycodone hydrochloride. Dilute to the mark with 8% sodium sulfate solution, shake well, centrifuge, accurately measure 1ml of the supernatant, place it in a 10ml volumetric flask, dilute to the mark with the mobile phase, and shake well.
[0201] Take appropriate amounts of acetaminophen and oxycodone hydrochloride reference standards, accurately weigh them, dissolve them in the mobile phase, and quantitatively dilute them to prepare a mixed solution containing approximately 130 μg of acetaminophen and 2 μg of oxycodone hydrochloride per ml.
[0202] The chromatographic conditions were as follows: octylsilane-bonded silica gel was used as the stationary phase; the mobile phase was [sodium hexanesulfonate 0.005 mol / L, pH adjusted to 4.0 with 0.1% triethylamine phosphoric acid]-methanol-acetonitrile (75:10:15); the flow rate was 1.5 mL / min; the column temperature was 40 °C; the detection wavelength was 214 nm; and the injection volume was 10 mL.
[0203] The content of acetaminophen and oxycodone hydrochloride in each tablet was measured, and the content uniformity of 10 tablets was calculated.
[0204] Calculation method:
[0205] According to the requirements of General Chapter 0941 of Part IV of the 2025 edition of the Chinese Pharmacopoeia, take 10 test samples and determine the relative content of each single dose with the labeled amount as 100 according to the methods specified under each variety. Calculate the mean X and standard deviation S, as well as the absolute value A of the difference between the labeled amount and the mean (A=|100-x).
[0206]
[0207] 3. Observation results:
[0208] The results of the investigation are shown in Table 21.
[0209] Table 21 Results of Mixing Homogeneity
[0210]
[0211] The results in Table 21 show that the sustained-release granules, immediate-release granules, and tablets prepared by the method of separately granulating oxycodone hydrochloride and acetaminophen in the samples of the present invention (such as Example 2) all meet the requirements for mixing uniformity (RSD value < 5.0%, A+2.2S < 15), indicating good mixing uniformity. However, the RSD values of sustained-release granules, immediate-release granules, and tablets prepared directly from oxycodone hydrochloride powder and acetaminophen powder (Comparative Example 5), or the RSD values of sustained-release granules, immediate-release granules, and tablets prepared by granulating oxycodone hydrochloride and then mixing it with acetaminophen powder (Comparative Example 6) are all greater than 5%, and A+2.2S > 15, indicating poor mixing uniformity.
[0212] Furthermore, comparing the mixing uniformity data of Examples 2 and 4-6 shows that the amount of hydroxypropyl cellulose in the sustained-release layer (especially the weight ratio of polyoxyethylene to hydroxypropyl cellulose) affects the mixing uniformity of the tablets. For example, when the weight ratio of polyoxyethylene to hydroxypropyl cellulose in the sustained-release layer is between 15:1 and 30:1 (as in Examples 2 and 4-6), the mixing uniformity of the sustained-release layer particles, immediate-release layer particles, and tablets all meet the requirements (RSD value < 5.0%, A+2.2S < 15). However, in Comparative Examples 1 and 2, the RSD values of the sustained-release layer particles, immediate-release layer particles, and tablets are all greater than 5%, and A+2.2S > 14, indicating poor mixing uniformity. In addition, all test indicators, including the mixing uniformity, of the samples prepared in Examples 1, 3, and 7 of this invention meet the requirements.
[0213] Example 3
[0214] Evaluation of tablet stability
[0215] 1. Sample
[0216] Sample of this invention: The sample prepared in Example 2;
[0217] Comparative formulation samples: Samples prepared in comparative examples 5 and 6.
[0218] 2. Test methods:
[0219] Samples were placed under high temperature and high humidity (40℃±2℃, RH75%±5%) conditions and tested for impurity content, friability, and properties in the 3rd and 6th months, respectively. Samples were taken under high temperature (60℃±2℃) conditions on the 10th and 30th days, respectively, and tested for impurity content, friability, and properties.
[0220] Test equipment: DHG-9240A electric thermostatic drying oven, SHH-1000SD drug stability test chamber.
[0221] Testing instrument: High performance liquid chromatograph (Agilent 1260).
[0222] Chromatographic conditions:
[0223] Chromatographic column: octadecylsilane-bonded silica gel (Kromasil 4.6mm × 150mm, 5μm) was used as the packing material.
[0224] Mobile phase: Acetonitrile-buffered buffer (7.8 g / L potassium dihydrogen phosphate, pH adjusted to 3.0 with phosphoric acid) 10:90.
[0225] Wavelength: 206nm.
[0226] Column temperature: 40℃.
[0227] Flow rate: 1.0 ml / min.
[0228] Volume: 20 μl.
[0229] Concentration: 0.5 mg / ml.
[0230] 3. Observation results:
[0231] The results of the investigation are shown in Tables 22 and 23.
[0232] Table 22 Results of Stability Study under High Temperature and High Humidity Tests
[0233]
[0234] Table 23 Results of High Temperature Test Stability Assessment
[0235]
[0236] The results in Tables 22-23 show that the samples of the present invention (such as Example 2) exhibit superior stability of the active ingredient under high temperature and high humidity and high temperature stability testing conditions. They demonstrate a significant comprehensive control effect on degradation impurities such as 14-hydroxycodeinone, oxycodone nitrogen oxides, and oxycodone dimers, and exhibit low friability with no tablet breakage. In contrast, samples prepared directly from oxycodone hydrochloride powder and acetaminophen powder (Comparative Example 5), or samples prepared by granulating oxycodone hydrochloride and then mixing it with acetaminophen powder (Comparative Example 6), show a significant increase in degradation impurities such as 14-hydroxycodeinone, oxycodone nitrogen oxides, and oxycodone dimers under high temperature and high humidity and high temperature stability testing conditions, along with increased friability and the appearance of tablet breakage and cracks. Furthermore, the samples prepared in Examples 1, 3-7 of the present invention meet the requirements for all test indicators, including active ingredient stability, tablet friability, and appearance, under high temperature and high humidity and high temperature stability testing conditions.
[0237] Therefore, the sample of the present invention has a better overall impurity control capability, which can effectively reduce the medication risk that may be caused by the accumulation of degradation impurities, and reduce the problem of drug quality decline due to brittleness and changes in properties during storage. The sample of the present invention has a better brittleness control effect and does not have the problem of double-layer tablets breaking.
[0238] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. A sustained-release tablet of acetaminophen and oxycodone, characterized in that, The acetaminophen-oxycodone sustained-release tablet comprises a sustained-release layer and an immediate-release layer. By weight, the sustained-release layer comprises 3.5-4 parts of oxycodone hydrochloride and 130-195 parts of acetaminophen, and the immediate-release layer comprises 1-1.5 parts of oxycodone hydrochloride and 130-195 parts of acetaminophen. The sustained-release layer is formed by mixing and pressing oxycodone hydrochloride particles, acetaminophen particles, and excipient A. The immediate-release layer is formed by mixing and pressing oxycodone hydrochloride particles, acetaminophen particles, and excipient B. The oxycodone hydrochloride particles are granulated from 4.5 to 5.5 parts of oxycodone hydrochloride and excipient A. The acetaminophen particles are granulated from 260 to 390 parts of acetaminophen and excipient B. The internal excipient A contains 10-30 parts of microcrystalline cellulose, the internal excipient B contains 20-60 parts of microcrystalline cellulose and 15-40 parts of hydroxypropyl cellulose, the external excipient A contains 200-350 parts of polyoxyethylene, and the external excipient B contains 2-10 parts of crosslinked sodium carboxymethyl cellulose. The acetaminophen particles have a D90 of 360-560 μm and a D50 of 110-180 μm; the polyoxyethylene has a molecular weight of 1,000,000-2,000,000.
2. The acetaminophen / oxycodone sustained-release tablet according to claim 1, characterized in that, The total weight of oxycodone hydrochloride in the acetaminophen-oxycodone sustained-release tablets is 5 parts, and the total weight of acetaminophen is 325 parts.
3. The acetaminophen / oxycodone sustained-release tablet according to claim 1, characterized in that, In the acetaminophen granules, the weight ratio of acetaminophen to hydroxypropyl cellulose is 10:1 to 20:
1.
4. The acetaminophen / oxycodone sustained-release tablet according to claim 1, characterized in that, In the oxycodone hydrochloride particles, the weight ratio of oxycodone hydrochloride to microcrystalline cellulose is 1:3 to 1:
6.
5. The acetaminophen / oxycodone sustained-release tablet according to claim 1, characterized in that, The internal additive A further includes one or more of pregelatinized starch, anhydrous citric acid, and disodium edetate; the external additive A further includes one or more of microcrystalline cellulose, colloidal silica, and magnesium stearate; and the external additive B further includes one or more of hydroxypropyl cellulose, microcrystalline cellulose, colloidal silica, and magnesium stearate.
6. A method for preparing acetaminophen-oxycodone sustained-release tablets as described in any one of claims 1 to 5, characterized in that, The preparation method includes the following steps: a. Prepare oxycodone hydrochloride granules by weighing oxycodone hydrochloride and excipient A according to the prescription weight parts, and prepare acetaminophen granules by weighing acetaminophen and excipient B according to the prescription weight parts; b. Weigh the granules from step a according to the prescription weight parts, add excipient A, and mix to prepare sustained-release granules; c. Weigh the granules from step a according to the prescription weight parts, add excipient B, and mix to prepare immediate-release granules; d. Press a double-layer tablet core consisting of sustained-release and immediate-release particles; e. Double-layer core is coated.
7. Use of the acetaminophen-oxycodone sustained-release tablets as described in any one of claims 1 to 5 in the preparation of a medicament for treating pain.
Citation Information
Patent Citations
Gastric retentive extended-release dosage forms comprising combinations of a non-opioid analgesic and an opioid analgesic
CN102105136A
Morphinaloxone pharmaceutical composition and application thereof
CN121818643A